2022
DOI: 10.1021/acs.bioconjchem.2c00379
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Micelles Outperform Linear Polymers for Delivery of Antisense Oligonucleotides in Serum: An Exploration of Polymer Architecture, Cationic Moieties, and Cell Addition Order

Abstract: Antisense oligonucleotides (ASOs) are an important emerging therapeutic; however, they struggle to enter cells without a delivery vehicle, such as a cationic polymer. To understand the role of polymer architecture for ASO delivery, five linear polymers and five diblock polymers (capable of self-assembly into micelles) were synthesized with varying cationic groups. After complexation of each polymer/micelle with ASO, it was found that less bulky cationic moieties transfected the ASO more effectively. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…For example, it has been shown in literature that adding spacers can modify the p K a of polymers and affect binding . There are already plenty of excess positive charges (due to the high N/Ps), so binding appears to not be affected by changes in p K a and is affected more by the moiety substitution pattern and steric hindrance, a trend seen before in literature. , …”
Section: Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…For example, it has been shown in literature that adding spacers can modify the p K a of polymers and affect binding . There are already plenty of excess positive charges (due to the high N/Ps), so binding appears to not be affected by changes in p K a and is affected more by the moiety substitution pattern and steric hindrance, a trend seen before in literature. , …”
Section: Results and Discussionmentioning
confidence: 73%
“…Next, these systems were studied for their delivery of ASOs in vitro . A GFP knockdown assay was used to study delivery efficacy. ,, Briefly, HEK cells that have been modified to continually produce destabilized GFP (deGFP) were lifted using trypsin and then added to micelleplexes containing an ASO that would knock down deGFP mRNA and prevent it from being translated into the protein. Importantly, these transfections were all completed under conditions containing serum.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The successful delivery and gene silencing for ASO payloads is reliant on polycation-polyanion electrostatic association and complexation. Previous work from our group has already demonstrated that both D and D-BMA micelles bind well with ASOs across a large range of N/Ps or the molar ratio of nitrogen atoms from the cationic block to the phosphorothioates within the ASOs. , To analyze the binding capacity of this family, the small fluorescent probe OliGreen was used to quantify the strength of binding. OliGreen fluoresces when bound to ssDNA, but will get excluded if polymers and micelles bind to the ASO causing a decrease in fluorescence.…”
Section: Resultsmentioning
confidence: 99%
“…One key discovery has been the importance of complex architectures such as micelles (termed micelleplex when complexed with genetic material) for better delivery. [38][39][40][41][42] The cationic nature of these materials suggests that they may also interact favorably with bacterial cells 2,20,28,[43][44] . In addition, the ease of synthesis of these types of molecules could make them a promising new class of bacterial delivery reagents.…”
Section: Introductionmentioning
confidence: 99%
“…One key discovery has been the importance of complex architectures such as micelles (termed micelleplex when complexed with genetic material) for better delivery. 3842…”
Section: Introductionmentioning
confidence: 99%